MENGATASI KEKERASAN PADA ANAK DALAM PENDIDIKAN DI SEKOLAH (Forum Ilmu Sosial, 2012)
Children are the next generation to achieve the ideals of family, nation andcountry who have a strategic role in ensuring the existence of the nation and the state in the future, therefore, they should be free from any violence. Violence against children often happens in education at schools, both physical and non-physical (psychic). To minimize the occurrence of violence in the educational environment, the school, especially the teachers can select and use a more humanistic approach to learning by considering various dimensions to be achieved in the National Educational Objectives. One alternative to reduce the violence in the educational environment, educators or teachers can be the use of the PAKEM learning model with Child Friendly Teaching Model (CFTM) or 3P-based learning model (Provision, Protection and Participation).